Extracellular and intracellular activities of clarithromycin used alone and in association with ethambutol and rifampin against Mycobacterium avium complex. - Rastogi, N (1991)
Mycobacterium avium complex bacteria are opportunistic human pathogens, and their chemotherapy remains a challenge since these organisms are resistant to a majority of routine antituberculous drugs. Recently, a wide range of new macrolide antibiotics has been developed, among which the drug clarithromycin appears to have a selective action against M. avium bacteria. In the present study, we have investigated the action of clarithromycin alone (MIC and MBC determinations) and in association with the routine antimycobacterial drugs ethambutol and rifampin at sublethal concentrations (1 micrograms/ml; below concentrations obtainable in human serum) against M. avium. Our viable count data showed that clarithromycin was bactericidal against all 10 strains of M. avium studied and that its activity was enhanced by ethambutol (in 8 of 9 strains) and rifampin (in 3 of 9 strains). The use of all three drugs in association resulted in higher bactericidal effects than found with any of the drugs used alone or in two-drug combinations in seven of nine strains. The bactericidal effects of various drugs used alone and in combination at concentrations obtainable in human serum were investigated against the type strain ATCC 15769 by using 7H9 broth and BACTEC radiometry (extracellular action) and a J-774 macrophage cell line (intracellular action). A good agreement between the extracellular and intracellular activities was found. Electron microscopy using a ruthenium red cytochemical staining of the bacteria showed that clarithromycin disorganized the outer wall layer and the cytoplasmic membrane in the mycobacterial cell envelope and resulted in formation of large vacuoles inside the cytoplasm, with solubilization of ribosomal structures and consequent plasmolysis. Its association with ethambutol and rifampin resulted in more drastic alterations in the bacterial morphology than were seen with any of the drugs used alone, leading to the removal of the bacterial outer layer, homogenization of cytoplasm, complete cell lysis, and formation of ghosts.